VD_FINDINFO HC / 2015 / 188 vom 12. März 2015 - VD Tribunal cantonal (2015)
GARDE ALTERNÉE, DIVORCE, RELATIONS PERSONNELLES, EXPERTISE | 133 al. 1 CC, 133 al. 2 CC, 273 al. 1 CC, 273 CC, 275 CC, 106 al. 1 CPC (CH), 106 al. 2 CPC (CH)